2023
DOI: 10.3171/2022.10.jns221183
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-oncology authorship trends in gender since 1944: a systematic review of 14,020 articles from five top-tier academic journals

Abstract: OBJECTIVE This study was performed to compare authorship trends, by gender, in the neurosurgical oncology literature. METHODS Complete author listings for neurosurgical oncology articles published between 1944 and 2021 in five top neuro-oncology journals were extracted from the PubMed database and journal websites on December 2, 2021. Author gender was characterized with the web application programming interface (API) genderize.io. The statistical significance (p < 0.05) of time-, journal-, and gender-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
1
1
Order By: Relevance
“…In contrast to this study, where no significant gender disparity was found in the analysed journals, a systematic review examining the authorship trends in Neuro-oncology in academic journals since 1944 by Behmer Hansen et al (2022) found that the percentage of female first and last authors in medically oriented journals demonstrated a more noticeable increase rate (0.72% vs. 0.36% per year) in comparison to surgically oriented journals [14].…”
Section: Figure 3: the Gender Trend In Publications Based On Countriescontrasting
confidence: 92%
“…In contrast to this study, where no significant gender disparity was found in the analysed journals, a systematic review examining the authorship trends in Neuro-oncology in academic journals since 1944 by Behmer Hansen et al (2022) found that the percentage of female first and last authors in medically oriented journals demonstrated a more noticeable increase rate (0.72% vs. 0.36% per year) in comparison to surgically oriented journals [14].…”
Section: Figure 3: the Gender Trend In Publications Based On Countriescontrasting
confidence: 92%
“…However, because self-reported gender data is unavailable, we propose that our approach provides a reasonable method that is in alignment with similar studies. [23][24][25] Metadata for these preprints and articles was analyzed using descriptive statistics.…”
Section: Data Collectionmentioning
confidence: 99%